Analysis of Causes and Strategies to Overcome Low Literacy Levels at Mts Al Hidayah - Hamidah; Ade Jamarudin; Imam Sucipto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Literacy skills are an important foundation in character building and mastery of knowledge in the 21st century. According to a survey conducted by the Program for International Student Assessment (PISA) in 2022, it was revealed that the literacy rate in Indonesia is still relatively low and is a major challenge, especially in the education sector. The purpose of this study is to analyze the problems and determine the factors that cause low levels of student literacy and to develop strategies to foster reading literacy habits among students at MTs Al Hidayah. The research methods used include observation, interviews and literature reviews. The results of this study explain that internal factors such as lack of motivation and low interest in reading, as well as external factors such as technological advances and developments that divert students' attention and limited literacy facilities are the main obstacles to low student interest in reading. The solution is to overcome low student literacy by implementing the School Literacy Movement (GLS), optimizing library facilities, and the importance of the active role of teachers in cultivating reading, as well as synergy between families, schools, and communities in order to encourage the growth and development of literacy in the school environment and build a generation with more character. To follow up on the results of this study, recommendations are needed from various institutions.